2018
DOI: 10.1155/2018/6214095
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Resting-State Connectivity following Melody-Based Therapy in a Patient with Aphasia

Abstract: Melody-based treatments for patients with aphasia rely on the notion of preserved musical abilities in the RH, following left hemisphere damage. However, despite evidence for their effectiveness, the role of the RH is still an open question. We measured changes in resting-state functional connectivity following melody-based intervention, to identify lateralization of treatment-related changes. A patient with aphasia due to left frontal and temporal hemorrhages following traumatic brain injuries (TBI) more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…This hypothesis is supported by findings from brain stimulation studies, wherein the suppression of specific regions in the right hemisphere in non-fluent aphasia resulted in improved language performances [15][16][17][18]. In contrast, other studies suggest that the increased involvement of the right hemisphere (RH) in language processing following left hemisphere damage reflects compensatory supportive processes [8,[19][20][21][22][23][24][25]. Recent work by Kiran et al [26] suggests that although spared tissue within the left hemisphere is critically engaged in language recovery, right hemisphere regions are also involved in this process.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This hypothesis is supported by findings from brain stimulation studies, wherein the suppression of specific regions in the right hemisphere in non-fluent aphasia resulted in improved language performances [15][16][17][18]. In contrast, other studies suggest that the increased involvement of the right hemisphere (RH) in language processing following left hemisphere damage reflects compensatory supportive processes [8,[19][20][21][22][23][24][25]. Recent work by Kiran et al [26] suggests that although spared tissue within the left hemisphere is critically engaged in language recovery, right hemisphere regions are also involved in this process.…”
Section: Introductionmentioning
confidence: 82%
“…It is widely accepted that analysis of brain connectivity is of significant importance to the understanding of brain plasticity [3,43,44]. Changes in functional connectivity among PWA have been reported in several studies [45][46][47][48], and specific changes in the language network have been detected following language therapy [21,49,50]. Effective connectivity, which refers to the causal influence that neural populations exert on each other and can be inferred from fMRI data, has been analyzed in several language studies in healthy individuals [42,[51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…In aphasia, melody-based treatments rely on the notion that they can induce structural white matter neuroplasticity and that right hemisphere (with preserved musical abilities) can have compensatory role. Bitan et al [ 11 ] show how the use of melody-based treatment results in increased connectivity between motor speech control areas (bilateral supplementary motor areas and insulae) and right hemisphere language areas (inferior frontal gyrus pars triangularis and pars opercularis). Sihvonen et al [ 12 ] found that a 3-month neurological music therapy treatment resulted in increased quantitative anisotropy (QA) in the right dorsal pathways (arcuate fasciculus and superior longitudinal fasciculus) and in the corpus callosum and the right frontal aslant tract, thalamic radiation and corticostriatal tracts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent fMRI investigations have also shown that the right hemisphere plays a key role in MIT treatment. For example, Bitan et al [18] analyzed resting-state fMRI data gathered before and after MIT therapy and found that the connection between bilateral motor speech control areas and right-hemispheric “language center” (inferior frontal gyrus, pars triangularis, and pars opercularis) had improved.…”
Section: Introductionmentioning
confidence: 99%